Management Models of the Manila Clam (Ruditapes philippinarum) Fisheries in Invaded European Coastal Systems - Coelho, Pedro; Carvalho, Frederico; Goulding, Thomas; Chainho, Paula; Guerreiro, José (Frontiers in Marine Science, 2021)
The Manila clam (Ruditapes philippinarum, Adam & Reeve 1850) is a non-indigenous species that was introduced in Europe (France) in the 1970s for commercial purposes, and reached Portugal in the 1980s. Currently, it occurs in several European coastal systems, from the Bay of Biscay to the north Mediterranean. In Portugal, it is present in estuarine systems and coastal lagoons from the north to south, such as Ria de Aveiro, Óbidos Lagoon and Sado estuary, but a sharp rise in the prevalence of this species in the largest Portuguese estuary, the Tagus, resulted in the exponential growth of the number of harvesters and, consequently, an increase in the illegal exploitation of this resource. At least 1700 harvesters were estimated in this system and an annual catch volume of between around 4,000 and 17,000 t which corresponds to an annual value around €10,000,000 to €23,000,000 of sales. There is a general failure to comply with current legislation, both in relation to harvesting and marketing, as well as constraints arising from spatial planning instruments in force on the estuary. The failure to comply with sanitary standards for the exploitation and trade of bivalve mollusks presents a risk to public health and a social-economic issue resulting from this activity. The goal of this study is to propose management models for this activity with the aim of contributing to create a legal framework in which sustainable harvesting can be achieved, in the different systems where exploitation occurs. In order to accomplish this goal, the current state play, legal framework, regulation for harvesting and trade and relevant spatial planning instruments in Portugal are analyzed. In order to ascertain an adequate national management strategy, a variety of case studies in France, Spain and Italy were studied. The outcome is a management model which includes a co-management strategy of concessions as well as a mixed regime with concession areas and free areas. The creation of specific regulations; implementation of a co-management model with the active participation of harvesters; science-based regulation of a closed season and maximum daily quotas and an improved surveillance of the activity are recommended.